PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 42 PEKANBARU - Aldriyanti, Novi; Alpusari, Mahmud; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background in this research is the low science achievement of third grade students SDN 42 Pekanbaru. Average score of the students before the action has not reached the established KKM, the average score of students is 61,67 with KKM 70. Among 36 students, only 15 students who reached KKM with 70% classical completeness. This research is a Classroom Action Research (CAR) that conducted to improve science achievement of third grade students SDN 42 Pekanbaru by applying cooperative learning model type make a match. The data collected in this research are teacher activities, student activites, and learning result’s observation sheet. The average of students achievement before action was 61,67 increase to 74,86 in cycle I with increasing percentage 21,38%. In the cycle II increase to 85,97 with increasing percentage 39,40%. Teacher activity in cycle I of first meeting obtained percentage 75%, good category and at second meeting obtained percentage 83,33%, good category. While on cycle II of the first meeting obtained percentage 91,67%, very good category and second meeting obtained percentage 95,83%, very good category. Student activity in cycle I of first meeting obtained percentage 70,83%, good category and at second meeting obtained percentage 79,16%, good category. While on cycle II of the first meeting obtained percentage 87,50%, very good category and second meeting obtained percentage 95,83%, very good category. The result of the research in the third grade SDN 42 Pekanbaru proved that applying cooperative learning model type make a match improving students’ science achievement.Key Words : Cooperative learning model type make a match, learning outcomes science